2009
DOI: 10.3928/01477447-20090502-01
|View full text |Cite
|
Sign up to set email alerts
|

Patient Outcomes Following Anterior Cruciate Ligament Reconstruction: The Influence of Psychological Factors

Abstract: Despite reports demonstrating good-to-excellent results, only 65% to 70% of patients return to their preinjury level of sports activity following anterior cruciate ligament reconstruction. Psychological factors may contribute to this performance disparity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 26 publications
1
46
0
Order By: Relevance
“…7 Taken together, the results of the current study and of previous research suggest that other aspects of recovery, such as psychological factors, are also important for returning to sport and may have been underrecognized. 14,32 This study found that factors influencing athletes' prospective judgment of their ability to return to sport predicted returning to the preinjury level. This judgment involved the athlete taking into account his or her psychological readiness to return, his or her perception of control over the return, and a timeline for return, which supports the notion that individuals are more likely to engage in an activity when they perceive greater competence and therefore have higher self-efficacy in the particular activity.…”
Section: Discussionmentioning
confidence: 93%
“…7 Taken together, the results of the current study and of previous research suggest that other aspects of recovery, such as psychological factors, are also important for returning to sport and may have been underrecognized. 14,32 This study found that factors influencing athletes' prospective judgment of their ability to return to sport predicted returning to the preinjury level. This judgment involved the athlete taking into account his or her psychological readiness to return, his or her perception of control over the return, and a timeline for return, which supports the notion that individuals are more likely to engage in an activity when they perceive greater competence and therefore have higher self-efficacy in the particular activity.…”
Section: Discussionmentioning
confidence: 93%
“…13,31,33,[37][38][39] People with higher self-efficacy levels have more positive outcomes after rehabilitation because they have confidence in their ability to complete the tasks that are presented to them; this may, in turn, facilitate greater adherence to rehabilitation. 13,38,39 Rehabilitation programs that incorporate techniques such as positive selftalk and goal setting have been associated with increased adherence to home rehabilitation and greater perceived effort.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the focus of the orthopaedic literature has been on evaluating impairment-based outcomes, such as knee stability, after reconstruction as a measure of the success of the surgery, while non-physical factors, including psychological factors, have been under-researched 1 2. From an impairment perspective, patients recover physical function well after surgery 3.…”
Section: Introductionmentioning
confidence: 99%